Mechanisms Underlying the Anti-Inflammatory Activity of Bergamot Essential Oil and Its Antinociceptive Effects † - Lombardo, Giovanni Enrico (Plants (Basel), 2020)
Renewed interest in natural products as potential source of drugs led us to investigate on both the anti-inflammatory and anti-nociceptive activity of Citrus bergamia Risso et Poiteau (bergamot) essential oil (BEO). Carrageenan-induced paw edema in rats was used as an experimental model of inflammation. Because of the toxicity of furocoumarins, we performed our study by using the BEO fraction deprived of these compounds (BEO-FF). Treatment with BEO-FF led to a significant inhibition of paw edema induced by a sub-plantar injection of carrageenan. Moreover, histological examination of BEO-FF-treated rat paw biopsies showed a reduction of pathological changes typical of edema. Pre-treatment with BEO-FF significantly reduced interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α levels in the paw homogenates, as well as nitrite/nitrate and prostaglandin E(2) (PGE(2)) content in exudates. In addition, BEO-FF possesses antioxidant properties, as determined by cell-free assays. Furthermore, results of the writhing test showed that BEO-FF elicited a pronounced analgesic response, as demonstrated by a significant inhibition of constrictions in mice receiving acetic acid, with respect to control animals, whereas the results of the hot plate test suggested that the supra-spinal analgesia participates in the anti-nociceptive effect of BEO-FF. Our study indicates that BEO-FF exerts anti-inflammatory and anti-nociceptive effects, and suggests its potential role as an anti-edemigen and analgesic drug.